Models Data Analysis of the Subject’s Lifelong Learning - Manako, Alla F.; Manako, Volodymyr V. (Control systems and computers (Online), 2024)
Introduction. The modeling of a complex object “data analysis of learning of the subject throughout life”, supported by technology, is experiencing a special stage of its development, undergoing a great influx of potential opportunities and possibilities. induce a steady increase in digital capabilities for everyone, Numerous subjects implement the designated capabilities with different perspectives, goals, at different levels, stages, different approaches, methods, designs, languages, procedures, systems, processes, tools, services, standards The hidden problem It seems that this great potential has not yet been systematically realized throughout life. And therefore, a lot of existing knowledge, models and technologies are often not effectively translated into existing tools for everyone. In our research, modeling focuses at a high level of abstraction on the enhanced understanding of the subject of the strategy for direct development, the adoption of informed solutions to the selection, adaptation of existing and planned Innovative tools, methods, analytics of all types with the help of available management systems. Purpose. The purpose of this study is develop a formalized description with meaningful interpretations of basic system-forming elements, modeling constructs, a general model, inheritance models and a register of tasks to systematically improve understanding, progress of results, quality of products, services and making informed decisions for stakeholders based on methods and tools data analysis of learning of the subject throughout life. Methods. System methodology, methods of analogies, didactic methods. Results. On the basis of fundamental facts, ideas and systematic methodology, at the highest level of formalization, basic system elements, modeling constructs, a general model, inheritance models and a register of tasks are proposed and meaningfully interpreted in order to systematically improve understanding, progress, results, quality of products, services and acceptance reasoned decisions for interested parties based on methods and tools of of learning of the subject throughout life with the help of an accessible management system. Conclusion. Modeling and practical implementation of an extremely complex process, system <data analysis of learning and behavior of the subject throughout life> in the era of digital transformations requires a comprehensive solution to many complex problems such as understanding, scaling, protection of property, elimination of uncertainty, interoperability, harmonization of existing and planned official and de facto standards. Systematized application of constructions from mathematical theories allows to better see their behavior, destroys uncertainty, helps to scale solutions, etc. Therefore, a necessary condition, a requirement for systematic improvement of models is a complex interpretation of abstractions in the context of the specified problems, as well as their practical approbation using available control systems with the aim of identifying and disseminating best practices to interested parties. The main directions of further research: building models of learning oriented games as part of the developed model of the Register of tasks in order to improve the skills of subjects in relation to data analysis: such as critical thinking, problem solving, communication, subject knowledge, data visualization; research on best practices for using the Glossary.